Development of Bacterial Cellulose Herbal Wound Dressing - Lasopha, Pronrapat; Lasopha, Sudkamon (Trends in Sciences, 2024)
Wound dressings play an essential role in wound care and healing, but the price is expensive for patients who have to treat for a long time such as patients from burns, scalds, etc. The objective of the research is to develop a wound dressing made with bacterial cellulose and local herb that has antibacterial properties, is cheap, and can be created by yourself. The bacterial cellulose (BC) produced from Acetobactor xylinum using coconut water waste to reduce costs. Its structure was changed to bacterial cellulose nanocrystals (BCNC) by acid hydrolysis, dried in 2 methods: Oven dried at 50 °C (dy) or freeze dried (fd). Then, herbal dressings were produced as a composite BC with herbs in 2 forms: A solution, i.e. C. Odorata leaf extract solution and a colloid, i.e. C. hystrix essential oil nanocapsule. The results for the production of a wound dressing showed that fd-BCNC had good quality, good fiber dispersion, high porosity and no antibacterial activity. It is suitable as a primary or secondary wound dressing, that does not help in wound healing. When fd-BCNC was loaded with herbs in 2 forms, it was found to be stable at room temperature, water adsorption, water vapor permeability and inhibit Staphylococcus aureus and Escherichia coli. Especially fd-BCNC of nanocapsule of C. hystrix peel essential oil has the best antibacterial effect. Therefore, you can apply this developed wound dressing to herbs used specifically for healing wounds. Moreover, we believe that this research will be a database that can be expanded to commercial production. HIGHLIGHTS Bacterial cellulose is produced using coconut water waste as culture medium Freeze-dried Bacterial cellulose nanocrystals is a promising for non antibacterial wound dressing Freeze-dried Bacterial cellulose nanocrystals composite with herbs are a promising for anti-bacterial wound dressing GRAPHICAL ABSTRACT